Outcome of Bubble CPAP in Neonate with Respiratory Distress (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Continuous Positive Airway Pressure (CPAP) is a well-established mode of respiratory support in newborns. Bubble CPAP (bCPAP) is safe, efficacious and easy to use in preterm and term neonates with mild to moderate respiratory distress.Objectives: To find out the outcome of bCPAP in neonate with respiratory distress.Methods: This cross sectional study was conducted over 6 months in Bangladesh Shishu Hospital & Institute. Total 108 term and preterm neonates were enrolled who were presented with respiratory distress. Neonate with type II respiratory failure, congenital heart disease and structural malformations of lung and GI tract causing respiratory distress at birth and neonate needed intubatuin at birth were excluded. Detailed information were obtained in each case. Thorough clinical examinations were done. Relevant investigation reports were collected. All the information were recorded. Statistical analysis was done by using SPSS version 23.Results: In this study the mean age was found 43.3±43.1 hours with range from 2 to 204 hours. Majority 62(57.4%) patients were male and male female ratio was 1.3:1. Two third (66.7%) patients had birth weight ³2500 gm, 14(12.9%) had